Opinião pública sobre bem-estar animal na microrregião de Lavras-MG - ABRAHAO, Juliana J. A. (2015)
This search was performed in the region of Lavras – MG and the aim was to identify public opinion about animal welfare in the commercial creation. The research was developed with a semi structured questionnaire help, having 13 questions. They interviewed 373 people by a pseudo-random form. The number of interviewed who believe that animals feel cold, heat, fear or distress, totaling 97.3%, and those who believe that animals feel pain compute 99.0%. Regarding management practices rearing system causing suffering to animals, 81.8% of the interviewed believe that they suffer, 7.2% believe that they don´t and 11% doesn´t know. The proportion of participants who have heard of humane slaughter comprises 33.5%, as those who have not heard 66.5%, and the majority of respondents (85.3%) believe that slaughter causes suffering to animals. 72.4% of the interviewed people know what is animal welfare. The results of independence test showed that only the relationship between knowledge about animal welfare and the willingness participant to pay more for animal products knowing that they were created considering the welfare, It was significant (P = 0.00647). It was concluded that in the region of Lavras-MG is the beginning of a mobilization and awareness of the subject studied, being a significant number of people who know what is animal welfare. One can also see the awakening of concern with bad handling of animals, gaining followers and no longer more being seen only as marketing requirements, however, there is need for greater awareness of humane slaughter. These search results show that a differential final product, a quality meat of animal origin that have been created respecting the BEA are valued by consumers, who are willing to pay more for these products.